2017
DOI: 10.1159/000452952
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Serotype 2 <b><i>Streptococcus suis </i></b>Arginine Deiminase

Abstract: Background: Arginine deiminase (ArcA) has been speculated to facilitate the intracellular survival of Streptococcus suis under acidic conditions. However, the physical and biological properties and function of SS2-ArcA have not yet been elucidated. Methods: Recombinant SS2-ArcA (rSS2-ArcA) was expressed and purified using Ni-NTA affinity chromatography. Under various pH and temperature conditions, the enzymatic properties of purified rSS2-ArcA and crude native SS2-ArcA were determined. Results: The SS2-arcA-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…Meanwhile, the arcA gene was detected in 98.6% (212/215) of the studied strains. Arginine deiminase, encoded by the arcA gene, is described as a facilitating factor for S. suis survival under acidic conditions [26]. Previous studies have also identified a high frequency of this gene in invasive and respiratory S. suis strains isolated from swine and humans [27,28], which suggests that it is not a good virulence marker.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the arcA gene was detected in 98.6% (212/215) of the studied strains. Arginine deiminase, encoded by the arcA gene, is described as a facilitating factor for S. suis survival under acidic conditions [26]. Previous studies have also identified a high frequency of this gene in invasive and respiratory S. suis strains isolated from swine and humans [27,28], which suggests that it is not a good virulence marker.…”
Section: Discussionmentioning
confidence: 99%
“…After the in silico predictions, in vitro e cacy of PfADI as a potential anticancer drug candidate was validated, the arcA gene of PfADI was cloned and expressed in E. coli. Previously, ADI from various organisms viz Streptococcus sanguis, Lactococcus lactis, Enterococcus faecalis, M. arginini have been cloned and over-expressed in E. coli 3,[38][39][40] with diverse aims such as to understand its importance in cell growth, arginine metabolism or the role as anticancer candidate 41 . The arcA gene from two species of genus Pseudomonas namely P. aeruginosa and P. plecoglossicida have also been cloned in the E. coli host 31,42 .…”
Section: Discussionmentioning
confidence: 99%
“…ADI is the major enzyme of the arginine deiminase pathway in prokaryotes that serve as a non-glycolytic pathway for energy generation 2 . Besides energy production and arginine catabolism, ADI also protects the bacteria from acidic environment by generation of ammonia 3 . The enzyme is widely present in bacteria and few lower protozoa but has not been reported in mammals 4 .…”
Section: Introductionmentioning
confidence: 99%
“…ADS способствует выживанию бактерий в условиях дефицита кислорода и нутриентов, а также и при снижении рН среды в разных биологических нишах. В рамках этой системы АД катализирует гидролиз L-аргинина с образованием L-цитруллина и аммиака, поэтому активность фермента может приводить к истощению L-аргинина в микроокружении клеток организма-хозяина при инфекции [13,18,30].…”
Section: Introductionunclassified